Italian multicentre study on type A acute aortic dissection: a 33-year follow-up†. (26th February 2015) - Russo, Claudio F.; Mariscalco, Giovanni; Colli, Andrea; Santè, Pasquale; Nicolini, Francesco; Miceli, Antonio; De Chiara, Benedetta; Beghi, Cesare; Gerosa, Gino; Glauber, Mattia; Gherli, Tiziano; Nappi, Gianantonio; et al.
Abstract : OBJECTIVES: Despite substantial progress in surgical techniques and perioperative management, the treatment and long-term follow-up of type A acute aortic dissection (AAD) still remain a major challenge. The objective of this retrospective, multicentre study was to assess in a large series of patients the early and long-term results after surgery for type A AAD. METHODS: We analysed the preoperative, intraoperative and postoperative conditions of 1.148 consecutive patients surgically treated in seven large referral centres from 1981 to 2013. We applied to each patient three different multi-parameter risk profiles (preadmission risk, admission risk and post-surgery risk) in order to compare risk factors and outcome. Long-term Kaplan–Meier survival was evaluated. RESULTS: The median age was 64 years and the male population was predominant (66%). Identified diagnosis of collagen disease was present in 9%, and Marfan syndrome in 5%. Bicuspid aortic valve was present in 69 patients (6%). Previous cardiac surgery was identified in 10% of the patients. During surgery, the native aortic valve was preserved in 72% of the cases, including leaflet resuspension in 23% and David operation in 1.2%. Considering aortic valve replacement (AVR: 28%), bioprosthesis implantation was performed in 14.7% of the subjects. Neurological impairment at discharge was shown in 23% of the cases among which 21% of patients had new neurological impairment versus preoperative conditions. The overall 30-day mortality rate was 25.7%. All risk profiles remained independently associated with in-hospital mortality. During the available follow-up of hospital survivors (median: 70 months, interquartile range: 34–113, maximum: 396), cardiac-related death occurred in 7.9% of the subjects. The cumulative survival rate for cardiac death was 95.3% at 5 years, 92.8% at 10 years and 52.8% at 20 years. Severe aortic regurgitation (AR) (grade 3–4) at the time of surgery showed to be a significant risk factor for reintervention during the follow-up ( P < 0.001). Among risk profiles, only the preadmission risk was independently associated with late mortality after multivariate analysis. Unexpectedly, there was no difference in freedom from cardiac death between patients with and without AVR. CONCLUSIONS: Although surgery for type A has remained challenging over more than three decades, there is a positive trend in terms of hospital mortality and long-term follow-up. About 90% of patients were free from reoperation in the long term, although late AR remains a critical issue, suggesting that a thorough debate on surgical options, assessment and results of a conservative approach should be considered.